Discovery of markers of exposure specific to bites of Lutzomyia longipalpis, the vector of Leishmania infantum chagasi in Latin America. - Clarissa Teixeira; Regis Gomes; Nicolas Collin; David Reynoso; Ryan Jochim; Fabiano Oliveira; Amy Seitz; Dia-Eldin Elnaiem; Arlene Caldas; Ana Paula de Souza; Cláudia I Brodskyn; Camila Indiani de Oliveira; et al. (Public Library of Science (PLoS), 2010)
Sand flies deliver Leishmania parasites to a host alongside salivary molecules that affect infection outcomes. Though some proteins are immunogenic and have potential as markers of vector exposure, their identity and vector specificity remain elusive.We screened human, dog, and fox sera from endemic areas of visceral leishmaniasis to identify potential markers of specific exposure to saliva of Lutzomyia longipalpis. Human and dog sera were further tested against additional sand fly species. Recombinant proteins of nine transcripts encoding secreted salivary molecules of Lu. longipalpis were produced, purified, and tested for antigenicity and specificity. Use of recombinant proteins corresponding to immunogenic molecules in Lu. longipalpis saliva identified LJM17 and LJM11 as potential markers of exposure. LJM17 was recognized by human, dog, and fox sera; LJM11 by humans and dogs. Notably, LJM17 and LJM11 were specifically recognized by humans exposed to Lu. longipalpis but not by individuals exposed to Lu. intermedia.Salivary recombinant proteins are of value as markers of vector exposure. In humans, LJM17 and LJM11 emerged as potential markers of specific exposure to Lu. longipalpis, the vector of Leishmania infantum chagasi in Latin America. In dogs, LJM17, LJM11, LJL13, LJL23, and LJL143 emerged as potential markers of sand fly exposure. Testing these recombinant proteins in large scale studies will validate their usefulness as specific markers of Lu. longipalpis exposure in humans and of sand fly exposure in dogs.